2017
DOI: 10.1186/s40001-017-0246-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of arthroscopic biopsy in periprosthetic infections of the hip

Abstract: BackgroundDiagnosis of a low-grade periprosthetic joint infection (PJI) prior to revision surgery can be challenging, despite paramount importance for further treatment. Arthroscopic biopsy of synovial and periprosthetic tissue with subsequent microbiological and histological examination can be beneficial but its specific diagnostic value has not been clearly defined.Methods20 consecutive patients who underwent percutaneous synovial fluid aspiration as well as arthroscopic biopsy due to suspected PJI of the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…Hyman et al [65] described favorable results in a series of eight patients with late acute hip PJIs-all patients were, however, managed with chronic antibiotic suppression in addition to arthroscopic lavage. Arthroscopy has a limited role in the diagnostic workup of a painful prosthesis, allowing for inspection of the components in search of instability and wear, exclusion of non-infectious causes, visualization of the synovium, and retrieval of samples for microbiology and histology in selected cases [14,[66][67][68]. Importantly, arthroscopy is an invasive intervention, which is associated with a small risk of infection; therefore, the indication for diagnostic arthroscopy should be considered carefully.…”
Section: Arthroscopic Lavage For Treatment Of Pjimentioning
confidence: 99%
“…Hyman et al [65] described favorable results in a series of eight patients with late acute hip PJIs-all patients were, however, managed with chronic antibiotic suppression in addition to arthroscopic lavage. Arthroscopy has a limited role in the diagnostic workup of a painful prosthesis, allowing for inspection of the components in search of instability and wear, exclusion of non-infectious causes, visualization of the synovium, and retrieval of samples for microbiology and histology in selected cases [14,[66][67][68]. Importantly, arthroscopy is an invasive intervention, which is associated with a small risk of infection; therefore, the indication for diagnostic arthroscopy should be considered carefully.…”
Section: Arthroscopic Lavage For Treatment Of Pjimentioning
confidence: 99%
“…The most commonly used method is the comprehensive consideration of multiple tests to distinguish between aseptic loosening and PJI [1]. However, the combined test, which was more suitable for the diagnosis of PJI was unclear [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used method is the comprehensive consideration of multiple tests to distinguish between aseptic loosening and PJI [1]. However, the combined test, which was more suitable for the diagnosis of PJI was unclear [2,3].Previous studies have indicated that serum interleukin-6 (IL-6) seems to be a promising tool for the diagnosis of PJI [4,5], and a meta-analysis of 11 studies reported that the pooled sensitivity and specificity of serum IL-6 were 0.72 (95% confidence interval [CI], 0.63-0.80) and 0.89 (95% CI, 0.77-0.95), respectively [6]. In recent years, the combination of serum IL-6 and C-reactive protein (CRP)…”
mentioning
confidence: 99%
“…Although a variety of serum, synovial uid, periprosthetic tissue, and sonication uid tests are currently performed for the diagnosis of periprosthetic joint infection (PJI), there is no single indicator that can detect infection with 100% accuracy [1]. Combined tests appear to further improve the diagnostic value, although which combined test is more suitable for diagnosis remained uncleared [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus epidermidis (8) Cutibacterium acnes (3) Culture negative infection (3) Staphylococcus capitis (2) Staphylococcus haemolyticus (1) Polymicrobial infection (1) Staphylococcus auricularis (1) Micrococcus luteus (1) Forest plots of the diagnostic odds ratio for the combined method (a), IL-6 (b) and CRP (c).…”
mentioning
confidence: 99%